Influence of the Number of Axial Bexarotene Ligands on the Cytotoxicity of Pt(IV) Analogs of Oxaliplatin - Yulia N. Nosova; Ilia V. Zenin; Varvara P. Maximova; Ekaterina M. Zhidkova; Kirill I. Kirsanov; Ekaterina A. Lesovaya; Anna A. Lobas; Mikhail V. Gorshkov; Olga N. Kovaleva; Elena R. Milaeva; Markus Galanski; Bernhard K. Keppler; et al. (Bioinorganic Chemistry and Applications)
We present the synthesis and cytotoxic potencies of new Pt(IV) complexes with bexarotene, an anticancer drug that induces cell differentiation and apoptosis via selective activation of retinoid X receptors. In these complexes bexarotene is positioned as an axial ligand. The complex of one bexarotene ligand attached to Pt(IV) oxaliplatin moiety was potent whereas its counterpart carrying two bexarotene ligands was inactive.